TEKS DRAMA GONG SAMPIK ANALISIS BENTUK, FUNGSI, DAN MAKNA - I Wayan Sugita (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2020)
Research on the “Text Drama Gong Sampik Analysis Form , Function , and Meaning”, aimed to describe the structure of the building as well as the text examines the function and meaning of the text contained in the drama gong “Sampik” . This research uses , semiotic theory (Enraswara , 2008: 64) , the theory of the structure , (Teeuw , 1984: 135) . The method used in the stage of providing data using methods refer to the technical note . In addition, using interviews with recording techniques and record . Furthermore, in the stage of data analysis using descriptive analytic techniques are also used literally and idiomatically . At the stage of presentation of the data , the method used is an informal method of inductive and deductive techniques . The results showed that ; (1) analyzes the structure of the text form of drama that builds drama gong “Sampik” There are four, namely : prologue , stage , scenes , and dialogue, and the narrative structure of the play there are five: plot, characterization and characterization , setting , theme, and mandate. (2) the language and style of the language used in the text of the drama gong “Sampik”. (3) text functions drama gong “Sampik” there are some functions that are contained in each babaknya quote quote that reflects situation or social reality. (4) the meaning of the text drama gong “Sampik” This is a search for identity .